ChemInform Abstract: Catalytic Diazosulfonylation of Enynals Toward Diazoindenes via Oxidative Radical‐Triggered 5‐exo‐trig Carbocyclizations. Issue 34 (4th August 2016) - Hao, Wen‐Juan; Du, Yan; Wang, Dan; Jiang, Bo; Gao, Qian; Tu, Shu‐Jiang; Li, Guigen
Abstract: The novel diazosulfonation reaction proceeds via addition of sulfonyl radicals to the enynal triple bond followed by 5‐exo‐trig carbocyclization/H‐abstraction sequence to furnish unprecedented diazoindenyl sulfones.